2007
DOI: 10.2353/ajpath.2007.061275
|View full text |Cite
|
Sign up to set email alerts
|

CCL21 Expression Pattern of Human Secondary Lymphoid Organ Stroma Is Conserved in Inflammatory Lesions with Lymphoid Neogenesis

Abstract: CCL21 is a homeostatic lymphoid chemokine instrumental in the recruitment and organization of T cells and dendritic cells into lymphoid T areas. In human secondary lymphoid organs (SLOs), CCL21 is produced by cells distributed throughout the T zone, whereas high endothelial venules (HEVs) lack CCL21 mRNA. A critical question remains whether the development of ectopic lymphoid tissue (ELT) in chronic inflammation recapitulates the features of SLOs. Thus, we systematically investigated in situ the cellular sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 56 publications
5
68
1
Order By: Relevance
“…Furthermore, given the propensity of myofibroblasts to produce cytokines and chemokines that orchestrate intratissue migration and positioning of circulating lymphocytes [36], functional differences of FLS may also modulate the degree and pattern of leukocyte infiltration in RA synovia, and thus the quality of overall tissue inflammation. In line with this concept, we recently showed that smooth muscle actin-positive, CD45 -spindle-shaped stromal cells within synovial lymphocytic aggregates are the source of the T-cell/dendritic cell chemoattractant CCL21 [37]. Similarly, although phenotypic characterization is lacking, FLS from lymphocyte-rich tissues also express CXCL12 and interleukin (IL)-7, which are involved in immune cell retention and lymphoid-like microanatomic organization [38,39].…”
Section: Heterogeneity Of Individual Synovial Cell Populationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, given the propensity of myofibroblasts to produce cytokines and chemokines that orchestrate intratissue migration and positioning of circulating lymphocytes [36], functional differences of FLS may also modulate the degree and pattern of leukocyte infiltration in RA synovia, and thus the quality of overall tissue inflammation. In line with this concept, we recently showed that smooth muscle actin-positive, CD45 -spindle-shaped stromal cells within synovial lymphocytic aggregates are the source of the T-cell/dendritic cell chemoattractant CCL21 [37]. Similarly, although phenotypic characterization is lacking, FLS from lymphocyte-rich tissues also express CXCL12 and interleukin (IL)-7, which are involved in immune cell retention and lymphoid-like microanatomic organization [38,39].…”
Section: Heterogeneity Of Individual Synovial Cell Populationsmentioning
confidence: 91%
“…A characteristic feature of synovial T-cell-B-cell clusters is their possible further progression into follicular, noncapsulated structures sharing some morphologic features with secondary lymphoid organs, with detectable highendothelial venules, a vestige of the lymphoid stromal reticular network, and CD21 + germinal centers [37,42]. The process of immune cell organization within discrete lymphoid microenvironments in the context of chronically inflamed tissues, also known as lymphoid neogenesis, has received a great deal of attention over the past 10 years due to its possible pathophysiologic significance, and has already been reviewed in detail by our group [14].…”
Section: Heterogeneity Of Synovial Patterns Of Cell Infiltrationmentioning
confidence: 99%
“…The angiogenic effects of VEGF-A may be responsible for the increased number of blood vessels observed in SS salivary glands. 22,23 The enhanced angiogenesis was associated with an increased VEGF-A/VEGFR2 signaling, as demonstrated by the observation of an increased amount of phosphorylated VEGFR2 in SS salivary glands biopsies. Given the critical role of VEGFR2 signaling in angiogenesis, antiRo/SSA Abs-regulated VEGFR2 activation may represent an important mechanism in the control of angiogenesis in SS.…”
Section: Tace Is Involved In Vegf-a-dependent Angiogenesis Induced Bymentioning
confidence: 95%
“…Both immature and mature DCs are present in the RA synovium in about a 1:1 ratio. The immature cells are primarily located in the sublining or lining layer of the synovium and in the perivascular infiltrates, whereas mature DCs are associated with perivascular lymphocytic infiltrates (36,37). These perivascular DCs were suggested to originate from blood-derived precursors that migrated through the activated endothelium and received differentiation signals, such as GM-CSF and IL-13, within the joint (reviewed in Ref.…”
Section: Maturationmentioning
confidence: 99%